Investigating the neurobiology of maternal opioid use disorder and prenatal opioid exposure using brain organoid technology - Dwivedi, Ila; Haddad, Gabriel G. (Frontiers in Cellular Neuroscience, 2024)
Over the past two decades, Opioid Use Disorder (OUD) among pregnant women has become a major global public health concern. OUD has been characterized as a problematic pattern of opioid use despite adverse physical, psychological, behavioral, and or social consequences. Due to the relapsing-remitting nature of this disorder, pregnant mothers are chronically exposed to exogenous opioids, resulting in adverse neurological and neuropsychiatric outcomes. Collateral fetal exposure to opioids also precipitates severe neurodevelopmental and neurocognitive sequelae. At present, much of what is known regarding the neurobiological consequences of OUD and prenatal opioid exposure (POE) has been derived from preclinical studies in animal models and postnatal or postmortem investigations in humans. However, species-specific differences in brain development, variations in subject age/health/background, and disparities in sample collection or storage have complicated the interpretation of findings produced by these explorations. The ethical or logistical inaccessibility of human fetal brain tissue has also limited direct examinations of prenatal drug effects. To circumvent these confounding factors, recent groups have begun employing induced pluripotent stem cell (iPSC)-derived brain organoid technology, which provides access to key aspects of cellular and molecular brain development, structure, and function in vitro. In this review, we endeavor to encapsulate the advancements in brain organoid culture that have enabled scientists to model and dissect the neural underpinnings and effects of OUD and POE. We hope not only to emphasize the utility of brain organoids for investigating these conditions, but also to highlight opportunities for further technical and conceptual progress. Although the application of brain organoids to this critical field of research is still in its nascent stages, understanding the neurobiology of OUD and POE via this modality will provide critical insights for improving maternal and fetal outcomes.